Forming of the national strategy for regional budgets - A. A. Shatsky (Вестник университета, 2023)
The article studies tax and non-tax revenues, at the expense of which forming of the regional budgets’ revenue part is carried out. The revenues have been assessed and the experts’ works studying forming of effective regional policy for the constituent entities of the Russian Federation analyzed. The positive and negative factors influencing the growth and decline in total revenues of regional budgets have been revealed with regions rated by this indicator. A model for assessing and forecasting the dynamics of regional development has been proposed. New approaches to management methods and technologies in the formation of scientific and innovation potential parameters on the basis of calculations have been determined. It has allowed to make a conclusion about the differentiation of regions and weak development of scientific potential. In this regard, the mechanism for resource provision implementation of the subjects’ spatial development has been devised. It will ensure the innovative development of the regional economy real sector.